Power System Planning in India : Incorporating Environmental Externality Costs and Benefits - World Bank (Washington, DC, 2012)
This paper has been prepared in accordance with the terms of reference for a study on power system planning in India: incorporating externality costs and benefits. It reviews estimates of the external costs of power in international studies as well as in India and compares the figures available. It also comments on the validity of the external cost estimates available and the use made of them in power system planning and regulation both outside and inside India. The structure is as follows. Section two reviews the external cost estimates of electricity generation in the European Union (EU), and other countries. It also reports some recent work on the external costs associated with transmission. Some comments for the range of estimates are offered. Section three reviews a few studies on external costs for India and compares those with the international estimates. Section four discusses the use made of external cost data in power system planning and regulation both internationally and in India and makes some recommendations for possible reforms in the Indian case. Section five reviews the Indian and international estimates of external costs of hydro and section six does the same for resettlement and rehabilitation (RR) costs. Section seven offers some conclusions.